2019
DOI: 10.1097/sap.0000000000001849
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Health After Breast Reduction Surgery Using the Breast-Q, Short-Form 36, Breast-Related Symptoms Questionnaire, and Modified Breast Evaluation Questionnaire

Abstract: Introduction Breast hypertrophy is a condition associated with physical, psychological, and psychosocial problems. The primary aims of this study were to determine the impact of breast hypertrophy and the effects of breast reduction, performed on the basis of well-described inclusion criteria, on general and breast-related health, using both general and diagnosis-specific validated questionnaires. We used a prospective, longitudinal paired study design. A secondary aim was to analyze the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…Aesthetic outcome using ABNSW score that ranges between zero and 15, was evaluated by a median score of 11 and 10 with a total median score of 10 and nonsignificant differences between items' scores as determined by both judge surgeons with non-significant difference regarding the total score (Table 4). [14][15][16][17] and was significantly (p<0.0001) higher in comparison to median value of the preoperative score that was 12 (IQR: [11][12][13][14]. Preoperative BRASS score was negatively correlated, while was positively correlated with education level, and the correlation was significant with age and BMI, but was nonsignificant with education level.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Aesthetic outcome using ABNSW score that ranges between zero and 15, was evaluated by a median score of 11 and 10 with a total median score of 10 and nonsignificant differences between items' scores as determined by both judge surgeons with non-significant difference regarding the total score (Table 4). [14][15][16][17] and was significantly (p<0.0001) higher in comparison to median value of the preoperative score that was 12 (IQR: [11][12][13][14]. Preoperative BRASS score was negatively correlated, while was positively correlated with education level, and the correlation was significant with age and BMI, but was nonsignificant with education level.…”
Section: Resultsmentioning
confidence: 93%
“…These findings indicated the positive feedback effect of RM on patients' psychological status and go in hand with Lewin et al who reported that RM alleviates or minimizes macromastia-associated pain, improves or normalizes health and psychosocial self-esteem especially in women with high preoperative breast volumes and long SN-N distances who documented more satisfaction with the PO cosmetic result than women slightly obese or had average weight with breast volume about 1000 ml. 16 Moreover, Krucoff et al and Nuzzi et al found RM patients especially young women experience excellent breast-related QoL with high satisfaction with breasts and sexual wellbeing. 17,18 Crittenden et al reported statistically significant improvements in satisfaction with breasts, psychosocial well-being, sexual well-being and physical well-being scorings of patients with breast hypertrophy after RM in comparison to preoperative scores.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, body perception affects women both psychosocially and psychosexually 7 . Recent studies stated that women with breast hypertrophy problem have lower self-respect 4,5,10 . Janik et al 3 reported that body image dissatisfaction was a great problem for women with breast hypertrophy and shame, depression, and anxiety were associated with weak body image.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that breast hypertrophy is an important factor affecting the body perception and is associated with negative body image 4,[7][8][9][10][11] . In addition, it has been stated that the increase in breast size in women is associated with depression level 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the symptoms described impair health-related quality of life (HRQoL). A breast reduction (reduction mammaplasty) is considered effective at reducing physical and psychosocial symptoms and improving HRQoL [ 12 , 13 ]; however, similar effects are also achieved when a breast reduction is performed for cosmetic reasons and therefore it is difficult to distinguish which patients should be operated in the publicly funded healthcare system [ 14 , 15 ]. Moreover, there is no standardisation regarding the assessment and prioritising of functional problems, such as back pain, compared to non-functional problems, for example suffering due to appearance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%